Synthesis of Polymeric Membrane for Desalination Process - I Made Pendi Adi Merta; Deffry Danius Dwi Putra; Siti Nurkhamidah; Fadlilatul Taufany; Yeni Rahmawati (IPTEK Journal of Proceedings Series, 2015)
Cellulose acetate/polyethylene glycol 200 (CA/PEG) membrane with ration 80/20 (wt%) was modified with varying amount of silica in many concentration (1-5% w/v). CA/PEG-200 membranes were characterized for their hydrophilicity, functional groups and permeation properties. The increasing of CA at CA/PEG membrane make membrane more dense and hydrophilicity of membrane decreases. Membrane hydrophilicity, permeate flux, permeability, and salt rejection increase with the increasing of silica concentration in CA/PEG membrane. The experiment results show that the highest salt rejection was obtained when 5% silica was added into CA/PEG (80/20) membrane.